COMPARISON OF MATHEMATICAL CRITICAL THINKING SKILLS TAUGHT USING POWERPOINT AND POWTOON LEARNING MEDIA - Marniati Marniati; Chairuddin Chairuddin; Tahir Tahir (JME (Journal of Mathematics Education), 2024)
This study aims to determine: whether the critical thinking ability of mathematics students taught using powtoon learning media is better than the critical thinking ability of mathematics students taught using power point learning media. The population in this study were all seventh grade students of SMP IT Wihdatul Ummah Kolaka. Sampling was determined by saturated sampling technique, so that class VIIIA was obtained as experimental class I and class VIIIB as experimental class II. The data on students' mathematical critical thinking skills were collected using a test instrument given during the posttest. The results showed that the critical thinking ability of mathematics of students taught using power point learning media consisting of 13 students showed an average value (mean) of 72.308. While the critical thinking ability of mathematics students taught using powtoon learning media consisting of 16 students showed an average value (mean) of 76.801. This shows that the average critical thinking ability of students in teaching social arithmetic material for Experiment II class is slightly higher than the average critical thinking ability of students in Experiment I class. Furthermore, the results of hypothesis testing using the t-test have obtained the value of t (-0.892) < ttabel (1.703), indicating that H0 is accepted, inferentially this means that the critical thinking ability of mathematics students taught using powtoon learning media is not better than the critical thinking ability of mathematics students taught using power point learning media.